Wholegrain Food Acceptance in Young Singaporean Adults - Neo, Jia En (Nutrients, 2017)
Previous epidemiological evidence suggests that habitual consumption of whole grains is associated with reduction of disease risk. While wholegrain food consumption appears to be increasing in Singapore, it is still low, with more infrequent consumption noted in younger Singaporeans. Therefore, the primary objective of this study is to determine the knowledge of whole grains and barriers to consumption of wholegrain foods. Thirty participants (age range 21–26 year, 19 females) took part in two focus groups separated by a 2-week period in which participants trialled a range of wholegrain foods. Barriers towards whole grain consumption and experiences of products during this familiarization period were discussed during the focus groups and knowledge of whole grains was assessed by questionnaire. Potential barriers such as personal factors, product-specific factors and external factors were identified with sensory and habitual being stronger barriers. The whole grain familiarization period did not alter the taste expectations of the consumers but it did manage to increase acceptance for four of the wholegrain products tested (muesli, cookies, granola bars and wholewheat pasta). These findings suggest existing barriers to wholegrain food consumption should be considered by public health agencies and manufacturing companies.